Effects of Short-Term Ageing Temperature on Conventional and High-Temperature Properties of Paving-Grade Bitumen with Anti-Stripping and WMA Additives - Krzysztof Maciejewski (MDPI AG, 2021)
The presented study explores the effects of decreased temperatures utilized in rolling thin-film oven (RTFOT) laboratory short-term ageing of asphalt binders based on 35/50- and 50/70-penetration paving-grade bitumen. Additionally, the effects of three additives used with these binders at different concentrations are evaluated: liquid anti-stripping agent, liquid warm-mix additive, and solid warm-mix additive. The resulting asphalt binders were subjected to basic (penetration at 25 °C, softening point, dynamic viscosity) and functional high-temperature characterization (G*/sin(δ), high critical temperature, non-recoverable creep compliance). It was found that the decreased short-term ageing temperatures may detrimentally impact the high-temperature grade of bituminous binders, but this effect can be mitigated by the use of appropriate additives. What is more, it was found that bituminous binders may respond differently to the aforementioned factors. Based on the results, it is advised that asphalt binders intended for use in warm-mix asphalts should be thoroughly tested to appropriately simulate the mixture production process and its effects.